Manajemen Jaringan Internet di Dinas Kesehatan Provinsi Bali Dengan Menggunakan Hierarchical Token Bucket - Utama, I Gede Abi Yodita; Jaya Sasmita, I Gusti Ngurah Agung; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2020)
The digital age 4.0 brings changes in the use of the internet network. The needs of internet is no longer a secondary need but becoming a primary need. Utilization of the internet network at the Bali Government Department of Health Service is often not used wisely which is impacting the access and connectivity. In addition, it also disrupting services to the community. Internet network management is also not well managed here. Hierarchical Token Bucket (HTB) is a way of internet network management using packet scheduling such as bandwidth management to every client. HTB implementation is able to maximize unused bandwidth. As the result for that, it will improve service quality. Implementation of HTB with MikroTik at the Bali Government Department of Health results in an even distribution of bandwidth based on bucket size, priority, CIR and MIR values. The division also does not interfere with access and connectivity in each section / field.